Leone, Sabrina (2013) Characterisation of a personal learning environment as a lifelong learning toolSpringer (Berlin) isbn 978‐1‐4614‐6274‐3 102 pp e‐book £35.99 (paper £44.99) http://www.springer.com/education+%26+language/learning+%26+instruction/book/978‐1‐4614‐6273‐6. (17th October 2013) - Smyth, Robyn
Summary: Leone's little book is a highly academic exposition of Moodle 2.0, the personal learning environment (ple ), and of its potential to improve learner‐learner interaction, co‐creation, and sharing of both the formal and the informal knowledge needed for modern learners to be highly engaged. It could be worth borrowing if you are dedicated to innovation in online learning and/or want to know the theory behind the software. Robyn Smyth